2000
DOI: 10.1007/s007010070104
|View full text |Cite
|
Sign up to set email alerts
|

Defining the Role of Stereotactic Radiosurgery Versus Microsurgery in the Treatment of Single Brain Metastases

Abstract: Stereotactic radiosurgery (RS) and surgery have proved to be effective treatment modalities for brain metastasis. We followed 133 patients whose treatment for intracranial disease was either RS or a single surgical resection at the University of Vienna from August 1992 through October 1996. All patients who received additional Whole Brain Radiotherapy were included. This was a retrospective, case-control study comparing these treatment modalities. Sixty-seven patients were treated by RS and 66 patients were tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
67
0
11

Year Published

2004
2004
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 181 publications
(80 citation statements)
references
References 23 publications
2
67
0
11
Order By: Relevance
“…Послеоперационное облучение ложа опухоли (или ТОГМ) является обязательным после хирургической резекции, но не требуется после СРХ. В нескольких ретроспективных исследованиях [31][32] предполагается, что при проведении радиохирургии и хирургической резекции достигаются аналогичные результаты. Единственное рандомизированное иссле-дование [33] по сравнению СРХ и операции (в комби-нации с ТОГМ) у пациентов с солитарным метастазом в головной мозг не выявило различий в выживаемости или смертности от неврологических причин; при СРХ реже наблюдалась токсичность I-II степени.…”
Section: '2015unclassified
“…Послеоперационное облучение ложа опухоли (или ТОГМ) является обязательным после хирургической резекции, но не требуется после СРХ. В нескольких ретроспективных исследованиях [31][32] предполагается, что при проведении радиохирургии и хирургической резекции достигаются аналогичные результаты. Единственное рандомизированное иссле-дование [33] по сравнению СРХ и операции (в комби-нации с ТОГМ) у пациентов с солитарным метастазом в головной мозг не выявило различий в выживаемости или смертности от неврологических причин; при СРХ реже наблюдалась токсичность I-II степени.…”
Section: '2015unclassified
“…15,21) Two retrospective studies that compared the efficacy of radiosurgery and surgery showed better local control in the radiosurgery group and the same effect on survival for both groups. 96,124) Gamma knife radiosurgery has been widely utilized as a primary treatment or in combination with whole brain radiation therapy. Even with multiple brain metastases, gamma knife radiosurgery can be effective for selected patients.…”
Section: Clinical Applications I Metastatic Brain Tumors and Other Mmentioning
confidence: 99%
“…Another advantage of surgical resection is the pathologic confi rmation of the malignant nature of the lesion. Postoperative radiotherapy has demonstrated a decrease in the recurrence of brain metastases, a decrease in the mortality due to neurological deterioration and a delay in neurologic clinical deterioration [2,3].Radiosurgery has emerged as a non-invasive option to treat patients with 1-3 brain metastases, providing similar local control rates to surgery [4][5][6]. However, no randomised trial has compared the two approaches.…”
mentioning
confidence: 99%
“…Radiosurgery has emerged as a non-invasive option to treat patients with 1-3 brain metastases, providing similar local control rates to surgery [4][5][6]. However, no randomised trial has compared the two approaches.…”
mentioning
confidence: 99%